2020
DOI: 10.47203/ijch.2020.v32i02.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of Diabetes using the Indian Diabetes Risk Score in an urban resettlement colony of East Delhi

Abstract: Background- The burden of diabetes in India is expected to worsen in the coming years. Indian Diabetes Risk Score (IDRS) is a validated and cost‑effective tool to identify risk of developing diabetes among population. Objectives- To assess the risk of Type 2 Diabetes mellitus using the IDRS in adults aged 30 years and above and to study the association of risk of diabetes with other factors. Material & Methods- A cross-sectional study was conducted in Kalyanpuri area of East Delhi. Data collection was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…The overall mean age was 43.38±11.26 years with range 30-75 years in their study. 20 The mean age is 40.13±15 years was found in our study. Sarkar et al in their study found mean age of 33.1±8.15 years and majority 64% belonging to less than 35 years which was similar to our study.…”
Section: Discussionsupporting
confidence: 52%
“…The overall mean age was 43.38±11.26 years with range 30-75 years in their study. 20 The mean age is 40.13±15 years was found in our study. Sarkar et al in their study found mean age of 33.1±8.15 years and majority 64% belonging to less than 35 years which was similar to our study.…”
Section: Discussionsupporting
confidence: 52%
“…[ 17 ] A study conducted in an Urban Resettlement Colony of Delhi reported a lower proportion (5.3%) of low risk and 94.6% of the individuals with moderate and high risk. [ 18 ] Although both results were similar, our study had more participants with moderate risk followed by high risk. However, study conducted in the urban slums of Pune by Dudeja P, et al , reported a higher proportion (77.4%) of high risk individuals.…”
Section: Discussionmentioning
confidence: 51%
“…A study from Chennai had 37% and 45% of its participants at high risk and moderate risk, respectively [18]. Another similar study from North India revealed 43.3% of its respondents at moderate risk, while 51.4% at high risk; a Karnataka-based study found 57.2% of its participants to be at moderate risk and 33.8% at high risk [1, 19]. A similar study in rural Karnataka showed 14.84% to be at high risk and 73.19% to be at moderate risk; a study from rural Tamil Nadu showed 74.7% of its study subjects to be at moderate risk and 12.1% to be at high risk [10, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The number of diabetics around the world is expected to increase from 366 million cases in 2011 to 552 million cases by 2030 as per the International Diabetes Federation (IDF) if no suitable urgent action is taken [1].…”
Section: Introductionmentioning
confidence: 99%